EVALUASI TINGKAT KEPUASAN PENGGUNA MENGGUNAKAN MODEL HOT-FIT TERHADAP E-PROCUREMENT SISTEM INFORMASI MANAJEMEN PENGADAAN LANGSUNG (SIMPeL) DI UNIVERSITAS JAMBI - Rizki Ridha Utami (JUSS (Jurnal Sains dan Sistem Informasi), 2021)
the Direct Procurement Management Information System, which is abbreviated as SIMPeL, is anapplication built by the Ministry of Finance LPSE that is used for the direct procurement process.SIMPeL development is motivated by the difficulty in monitoring and reporting the implementationof direct procurement if it is carried out manually. This study aims to determine the results ofevaluating the level of satisfaction with the implementation of the Direct Procurement ManagementInformation System (SIMPeL) in terms of the Human-Organization Technology (HOT) Fit Model atJambi University. SIMPeL does not escape the measurement of user satisfaction. One of theuniversities that adopted SIMPeL is Jambi University. This evaluation method clarifies all thecomponents contained in the information system itself. The results of the evaluation in this studywere compiled based on the HOT FIT evaluation framework, starting from Human, Organizationand Technology. Based on the results of interviews with seven informants, it was found that usersatisfaction using SIMPeL has a positive effect on system quality on system use, system quality onuser satisfaction, information quality on system users, information quality on user satisfaction,service quality on system use, service quality on user satisfaction. users, user satisfaction with theuse of the system, system users with net benefits, user satisfaction with net benefits andorganizational structure on net benefits in HOT-FIT but in the quality of the system there are fewproblems related to maintenance that occurs in SIMPeL.